Two-dimensional calibration-free odds design for phase I drug-combination trials - Wang, Wenliang; Jin, Huaqing; Zhang, Yan Dora; Yin, Guosheng (Frontiers in Oncology, 2023)
In oncology, it is commonplace to treat patients with a combination of drugs that deliver different effects from different disease-curing or cancer-elimination perspectives.Such drug combinations can often achieve higher efficacy in comparison with single-drug treatment due to synergy or non-overlapping toxicity. Due to the small sample size, there is a growing need for efficient designs for phase I clinical trials, especially for drugcombination trials. In the existing experimental design for phase I drug-combination trials, most of the proposed methods are parametric and model-based, either requiring